Soft Robot-Assisted Minimally Invasive Surgery and Interventions: Advances and Outlook - Kwok, Ka-Wai; Wurdemann, Helge; Arezzo, Alberto; Menciassi, Arianna; Althoefer, Kaspar (Proceedings of the IEEE, 2022)
Since the emergence of soft robotics around two decades ago, research interest in the field has escalated at a pace. It is fuelled by the industry's appreciation of the wide range of soft materials available that can be used to create highly dexterous robots with adaptability characteristics far beyond that which can be achieved with rigid component devices. The ability, inherent in soft robots, to compliantly adapt to the environment, has significantly sparked interest from the surgical robotics community. This article provides an in-depth overview of recent progress and outlines the remaining challenges in the development of soft robotics for minimally invasive surgery.